2011
DOI: 10.1590/s0103-50532011000600022
|View full text |Cite
|
Sign up to set email alerts
|

Risk simulation of soil contamination by polycyclic aromatic hydrocarbons from sewage sludge used as fertilizers

Abstract: Este trabalho investigou a presença de 16 hidrocarbonetos policíclicos aromáticos (HPAs) em lodo de esgoto e em solo com aplicação de lodo como fertilizante agrícola e simulou o risco de contaminação por HPAs a longo prazo. As amostras foram extraídas usando diclorometano e em seguida com n-hexano em banho ultrassônico. A limpeza do extrato foi feita em coluna de alumina. As quantificações dos HPAs foram obtidas por cromatografia gasosa acoplada a um espectrômetro de massas (GC-MS/MS ion trap). Os resultados e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…StanczykMazanek et al (2009) stated that sludge is a significant source of PAHs in amended soil, and they found that the PAH content of soil increased as the sludge dose increased but that the PAH contents of plants grown in soil amended with sludge did not increase as the sludge dose increased. Ecological risk assessments have shown that the PAH concentrations that have been found in sludge pose clear risks to soil ecosystems amended with sludge (Ning et al, 2014;Paraiba et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…StanczykMazanek et al (2009) stated that sludge is a significant source of PAHs in amended soil, and they found that the PAH content of soil increased as the sludge dose increased but that the PAH contents of plants grown in soil amended with sludge did not increase as the sludge dose increased. Ecological risk assessments have shown that the PAH concentrations that have been found in sludge pose clear risks to soil ecosystems amended with sludge (Ning et al, 2014;Paraiba et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pueden provenir de diversas fuentes, como por ejemplo: agua de riego; residuos orgánicos parcialmente descompuestos (composta, basura orgánica, abonos), que se aplican frecuentemente debido a su bajo costo (Eaton et al, 2007); fertilizantes inorgánicos, plaguicidas, lodos residuales de origen municipal o industrial que pueden, por un lado, inhibir a la microbiota edáfica (Shivakumar et al, 2011) y, con ello, alterar procesos como la mineralización de materia orgánica y del aporte de nutrimentos a las plantas y, por otro lado, pueden ser absorbidos por las plantas y causar fitotoxicidad, o ser transferidos a la cadena alimentaria (Paraíba et al, 2011). …”
Section: Fuentes De Contaminación En Agricultura Urbanaunclassified
“…Analyses of PAHs have been conducted in many areas, such as air [13], soil [14,15], sediment [16], sludgy [17], river and wastewater [18][19][20], smoke products [21,22], cosmetic products [23] and foods [24][25][26][27][28][29]. Recently, various analytical methods of PAHs for herbal medicines characterized by diverse matrices have been reported as follows.…”
Section: Introductionmentioning
confidence: 99%